Factors Associated with Poor Health-Related Quality of Life in Physically Active Older People - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This study aimed to associate morphological variables and physical fitness with health-related quality of life (HRQoL) in physically active older people. A cross-sectional study was carried out that evaluated 470 older people (89.57% female) with a mean age of 70.13 ± 6.57 years, residing in two regions of Chile. Morphological variables (body weight, bipedal height, waist circumference, body mass index, and waist to height ratio), physical fitness through the Senior Fitness Test protocol, and HRQoL using the SF-36 questionnaire were obtained. Logistic regression analysis was used to identify risk factors between morphological variables and physical fitness associated with HRQoL. The main results indicated that overweight (OR = 1.52; p = 0.034), a waist circumference with risk (OR = 1.56; p = 0.021), poor performance in the back scratch tests (OR = 1.02; p = 0.008) and timed up-and-go (OR = 1.19; p = 0.040) increased the probability of having a low general HRQoL. Also, the low performance of chair stand and arm curl tests was associated with poor physical and social dimensions of HRQoL (p < 0.05). In conclusion, a low HRQoL in physically active older people is associated with both morphological and physical fitness factors. © 2022 by the authors.